2013
DOI: 10.1021/jp3100415
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Polymorphic Transitions in Crystalline Diborane Deduced by Comparison of Simulated and Experimental Vibrational Spectra

Abstract: We investigate and assign the pressure-induced structural transformations in crystalline diborane (B 2 H 6 ) observed spectroscopically by Song and co-workers (J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 19 publications
4
39
0
Order By: Relevance
“…It is worth noting that the mode marked by a solid circle shows red shift at 3.2 GPa, which can be explained as the increased bond length and smaller chemical force constant induced by pressure. 50 The evolution of the internal modes versus pressure in the range of 400-1800 cm -1 is depicted in Fig. 4(b), most of the internal modes show increasing frequencies when pressure is increased, and discontinuities are observed at 0.9 and 3.2 GPa, which is consistent with the changes in Raman spectra, suggesting the structural changes.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…It is worth noting that the mode marked by a solid circle shows red shift at 3.2 GPa, which can be explained as the increased bond length and smaller chemical force constant induced by pressure. 50 The evolution of the internal modes versus pressure in the range of 400-1800 cm -1 is depicted in Fig. 4(b), most of the internal modes show increasing frequencies when pressure is increased, and discontinuities are observed at 0.9 and 3.2 GPa, which is consistent with the changes in Raman spectra, suggesting the structural changes.…”
Section: Resultssupporting
confidence: 63%
“…With increasing pressure, most of internal modes shift gradually toward higher frequencies due to the decrease in bond lengths and increase in effective force constants. 50 However, remarkable changes are observed at 0.9 GPa. For example, the two modes marked by arrows (0.3 GPa) around 582 cm -1 related to the deformation of N-C=O show obvious variation in intensity.…”
Section: Resultsmentioning
confidence: 98%
“…211,212 The computed IR and Raman spectra of ten candidate phases that contained the molecular diborane unit were compared with those obtained experimentally. 216 This study showed that phase I corresponds to the β-diborane structure, and the best candidates for phases II and III possessed a P 2 1 /c symmetry lattice, but with different molecular orientations. Importantly, all of the experimental data was consistent with phases containing B 2 H 6 units, suggesting that transformation to the thermodynamically preferred products, cyclic oligomers and polymer chains, is kinetically hindered.…”
Section: Group 13: Icosagen Hydrides Boronmentioning
confidence: 77%
“…Early theoretical studies concluded that molecular boranes become thermodynamically unstable towards systems comprised of extended bonded networks by ∼100-300 GPa, and that a BH 3 analogue of AlH 3 would become metallic below 30 GPa. 215 Twenty years later DFT calculations 213,216 were carried out to help characterize the phases investigated in Refs. 211,212 The computed IR and Raman spectra of ten candidate phases that contained the molecular diborane unit were compared with those obtained experimentally.…”
Section: Group 13: Icosagen Hydrides Boronmentioning
confidence: 99%
“…Diborane, B 2 H 6 [61], is the simplest stable borohydride at ambient condition [62]. It has a ring-type molecular structure and has two-bridging hydrogens [63] (see Figure 1). Begue [64] used high-level calculations to investigate the anharmonic vibrational properties of this compound.…”
Section: Diborane B 2 Hmentioning
confidence: 99%